Complete Genome Sequence of Pseudoxanthomonas taiwanensis AL17 and its Potential Genes - Deviyanthi Nur Afifah; Leyla Novita Brigiyanti; Made Puspasari Widhiastuty; Elvi Restiawaty; Akhmaloka (Journal of Pure and Applied Microbiology, 2024)
Several reports on genome sequencing using Next Generation Sequencing (NGS) to identify the total genome were extensively carried out; however, genome identification on thermophilic microorganisms is still limited. In this report, genome identification of thermophilic microorganisms isolated from compost, namely Pseudoxanthomonas taiwanensis AL17, was carried out. The result showed that AL17 contains 3,064,463 bp with a GC content of 72.08%. The genome comprises 2,833 CDSs, 6 RNA (5S, 16S, and 23S), 48 tRNA genes, and 17 Pseudogenes. A comparison of the genome to data based on Average Nucleotide Identity from Dfast-qc shows that the genome is closely related to Pseudoxanthomonas taiwanensis. Further analysis discovers numerous genes coding for potential enzymes, including hydratase, transferase, dehydrogenase, exopeptidase and hydrolases. In addition, the genome exhibits a number of stress-tolerant genes. Detailed analysis of the hydrolase genes, especially for esterase and lipase, showed that the genome exhibits no true lipase but a lipolytic enzyme within the GDSL-type esterase/lipase motif. The genomic information provides an understanding of thermophilic genomes and their relevance to stress-tolerant adaptation and explores potential genes, especially for industrial applications.